NONPROFIT ORGANIZATIONS CONTRIBUTION TO INCREASING THE TRANSPARENCY OF PUBLIC PROCUREMENT IN INDONESIA - Wicaksono, Kristian Widya (Economic Faculty, Attahiriyah Islamic University, 2020)
The aim of this paper is to examine the contribution of Indonesian Corruption Watch (ICW) and the Indonesian Procurement Association or Ikatan Ahli Pengadaaan Indonesia (IAPI) as non-profit organizations to increase the transparency in the public organizations' budgets utilization especially in the procurement of goods and services. In collaboration with the Non-Ministry Government Institutions (LPNK) in Indonesia called the Lembaga Kebijakan Pengadaan Barang/Jasa Pemerintah (LKPP), these non-profit organizations developed